A critical study and analysis of journal metric â€œCiteScoreâ€, cluster and regression analysis - Varada Rajkumar, K; Adimulam, Yesubabu; Subrahmanyam, K (International Journal of Engineering and Technology, 2018)
In previous days the quality of journal is measured based on many metrics such as impact factor; SNIP(Source Normalized Impact Per paper),SJR( SCImago Journal Rank) and IPP(Impact Per Publication). It is very hard to find that the research papers to be published in which journal? CiteScore is a better way of measuring the citation impact of sources such as journals. CiteScore is a metrics product for journal from elsevier, using the citation data from the scopusdatabase to rank journals. CiteScore metrics is a comprehensive current and free metrics for source titles in scopus. Apart from Impact factor, CiteScore is becoming increasingly important in the context of evaluating metrics for all journals. CiteScore metrics are available for 37956 titles in scopus. It is not limited to journals as also conference proceedings, trade, publications and book series. The metrics are available 6 years period from 2011 to 2016. For a subset of CiteScore dataset clustering and regression algorithms can be implemented to study the data points that lie equally distant from one another.